Generation of an integrated Hieracium genomic and transcriptomic resource enables exploration of small RNA pathways during apomixis initiation. Issue 1 (December 2016) - Rabiger, David; Taylor, Jennifer; Spriggs, Andrew; Hand, Melanie; Henderson, Steven; Johnson, Susan; Oelkers, Karsten; Hrmova, Maria; Saito, Keisuke; Suzuki, Go; Mukai, Yasuhiko; Carroll, Bernard; et al.
Abstract Background Application of apomixis, or asexual seed formation, in crop breeding would allow rapid fixation of complex traits, economizing improved crop delivery. Identification of apomixis genes is confounded by the polyploid nature, high genome complexity and lack of genomic sequence integration with reproductive tissue transcriptomes in most apomicts. Results A genomic and transcriptomic resource was developed forHieracium subgenusPilosella (Asteraceae) which incorporates characterized sexual, apomictic and mutant apomict plants exhibiting reversion to sexual reproduction. Apomicts develop additional female gametogenic cells that suppress the sexual pathway in ovules. Disrupting small RNA pathways in sexualArabidopsis also induces extra female gametogenic cells; therefore, the resource was used to examine if changes in small RNA pathways correlate with apomixis initiation. An initial characterization of small RNA pathway genes withinHieracium was undertaken, and ovary-expressedARGONAUTE genes were identified and cloned. Comparisons of whole ovary transcriptomes from mutant apomicts, relative to the parental apomict, revealed that differentially expressed genes were enriched for processes involved in small RNA biogenesis and chromatin silencing. Small RNA profiles within mutant ovaries did not reveal large-scale alterations in composition or length distributions; however, a small number of differentially expressed, putative small RNA targets were identified. Conclusions The establishedHieracium resource represents a substantial contribution towards the investigation of early sexual and apomictic female gamete development, and the generation of new candidate genes and markers. Observed changes in small RNA targets and biogenesis pathways within sexual and apomictic ovaries will underlie future functional research into apomixis initiation inHieracium .